Öğretmen Adaylarının Toplumsal Cinsiyet Rollerine Yönelik Tutumlarının İncelenmesi - Durualp, Enver; Durualp, Enver (Dicle University, 2023)
Araştırmada, öğretmen adaylarının toplumsal cinsiyet rollerine yönelik tutumları bazı değişkenler açısından incelenmiştir. Bu araştırma, nicel yönteme dayalı tarama modelinde bir araştırmadır. Eğitim fakültesinde öğrenim gören toplam 317 öğrenci uygun örnekleme yöntemiyle araştırmanın çalışma grubunu oluşturmuştur. Verilerin toplanmasında “Genel Bilgi Formu” ve “Toplumsal Cinsiyet Rolleri Tutum Ölçeği” kullanılmıştır. Araştırmada veriler etik onay alındıktan sonra, yüz yüze yöntemle toplanmıştır. Verilerin analizinde frekans, yüzde, ortalama gibi betimsel istatistikler ile Kolmogorov-Smirnov, Mann Whitney U ve Kruskal Wallis testlerinden yararlanılmıştır. Yapılan analizlerde, öğrencilerin toplumsal cinsiyet rollerine ilişkin tutumlarının doğum yeri ve yaşadığı yere, doğduğu ve yaşadığı yerin gelişmişlik düzeyine, 18 yaşına kadar birlikte yaşadığı kişilere ve gelir algısına göre anlamlı farklılıklar olduğu bulunmuştur (p

In the study, teacher candidates' attitudes toward gender roles were examined in terms of various variables. This research follows a survey model based on quantitative methods. The research study group consisted of a total of 317 students studying at the Faculty of Education, selected through convenient sampling method. Data were collected using the "General Information Form" and the "Gender Roles Attitude Scale". In the study, data were collected by the face-to-face method after ethical approval was obtained. In the data analysis, descriptive statistics such as frequency, percentage, average, and Kolmogorov-Smirnov, Mann Whitney U, and Kruskal Wallis tests were used. The analysis revealed significant differences in teacher candidates' attitudes towards gender roles based on their place of birth, place of residence, the level of development in their birthplace and residence, the individuals they lived with until the age of 18, and their perception of income. Accordingly, it was found that those born in provincial and district centers had higher attitudes towards gender role in marriage; those born in developed areas had higher attitudes towards egalitarian gender role; those living in provincial centers had higher attitudes towards egalitarian gender role, female gender role, gender role in marriage and traditional gender role; those living in developed areas had higher attitudes towards egalitarian and traditional gender role; those living with their families until the age of 18 had higher attitudes towards egalitarian gender role and male gender role; and those with middle income perception had higher attitudes towards gender role in marriage and traditional gender role.
Examination of Teacher Candidates' Attitudes Together Gender Roles
Keywords: Other Fields of Education; Alan Eğitimleri